Building A Legal And Ethical Framework For Responsible Artificial Intelligence - Muhammad Soffa Marwa; Agustin Leni Magdalen Rohi Riwu (Journal of Law, Society and Living Norms, 2025)
This paper analyzes the urgency of developing a comprehensive legal and ethical framework for Artificial Intelligence (AI) in Indonesia. Alongside the rapid adoption of AI in which is projected to contribute significantly to the national Gross Domestic Product (GDP), there also emerge fundamental risks such as algorithmic bias, disinformation, privacy violations, and misuse for criminal purposes. The analysis reveals a significant gap between the pace of technological innovation and the maturity of national regulations. Existing instruments, such as the Electronic Information and Transactions Law (ITE Law) and the Personal Data Protection Law (PDP Law), have proven inadequate in addressing the specific challenges posed by AI. Meanwhile, existing ethical guidelines, such as Circular Letter (SE) of the Minister of Communication and Information Technology (Menkominfo) Number 9 of 2023, remain soft regulations without legally binding force. By conducting a comparative analysis of international frameworks, particularly the EU AI Act, this paper recommends adopting a risk-based approach as the foundation for AI policy in Indonesia. The main conclusion emphasizes the need to transition from reactive and fragmented regulation to a legal framework that is anticipatory, coherent, and binding (hard law), supported by the establishment of an independent oversight body and strong multi-stakeholder governance to ensure responsible AI utilization aligned with national values